THE ROLE OF ELECTRONIC CITY'S PERSUASIVE COMMUNICATION TO INCREASE SALES: A CASE STUDY OF THE KOTA KASABLANKA BRANCH - Erna Hasanah; RR Roosita Cendrakasih; Sultan Himawan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The retail industry plays a crucial role in Indonesia’s economy, contributing significantly to the Gross Domestic Product (GDP). The COVID-19 pandemic has shifted consumer behavior, marked by the increase in online shopping activities, declining purchasing power, and the need for retailers to adapt their business strategies. This condition requires companies to develop communication strategies that are not only informative but also persuasive, in order to build trust, foster loyalty, and influence purchasing decisions. Electronic City, as one of the largest modern electronic retail companies in Indonesia, faces challenges from the rapid growth of e-commerce and marketplaces that offer more competitive prices. To address these challenges, Electronic City implemented an omnichannel strategy by combining physical stores with digital platforms, supported by persuasive communication efforts such as product consultation services, the “shop safely from home” campaign, and promotional programs like 0% installment. This study aims to examine the role of persuasive communication in Electronic City’s efforts to increase sales, with a particular focus on its Kota Kasablanka branch. This research employs a descriptive qualitative method with a case study approach. Data were collected through interviews, observations, and documentation related to Electronic City’s communication strategies. The findings are expected to provide theoretical contributions to the study of marketing communication as well as practical recommendations for retail businesses in designing effective persuasive communication strategies in the digital era.